Peculiarities of Epidemiological Situation on Crimean Hemorrhagic Fever in the Russian Federation at the Current stage - A. Yu. Popova; A. N. Kulichenko; E. B. Ezhlova; N. D. Pakskina; N. F. Vasilenko; O. V. Maletskaya; D. A. Prislegina; A. S. Volynkina (Проблемы особо опасных инфекций, 2018)
Objective. The analysis of epidemiological situation on Crimean hemorrhagic fever (CHF) in the Russian Federation at the current stage, identification of ways to improve the epidemiological surveillance and prophylaxis of the disease. Materials and methods. Data from statistical documentation and results of annual epizootiological monitoring of the CHF natural focus provided by the Administrations of the Rospotrebnadzor, Centers of Hygiene and Epidemiology in entities of the Southern and the North-Caucasian Federal Districts, Reference Centre for CHF monitoring, Research Anti-Plague Institutions and Plague Control stations were used for work. Results and conclusions. The CHF epidemiological situation remains unstable, the cases of the disease (including fatal) are registered every year. High activity of the CHF natural focus persists. The northward expansion of CHF natural focus boundaries is observed. The main causes of the unfavorable CHF epidemiological situation are associated with increase in the numbers and period of activity of ticks Hyalomma marginatum due to favorable climatic conditions. The list of priority measures to stabilize the CHF epidemiological situation developed by the Rospotrebnadzor has resulted in decrease in CHF cases by 51.9 % in 2017 compared to 2016 across all the territory of the south of the Russian Federation. The CHF morbidity in 2018 was 1.5 times lower than the average multi-year values (72 CHF patients). The number of CHF cases in comparison to 2017 has decreased by 1.3 times in the Stavropol Territory and by 1.4 times in the Rostov Region. The CHF morbidity has increased in the Astrakhan Region (by 3 times) and Volgograd Region (by 2.3 times). Nosocomial CCHF virus infections cases associated with non-compliance to anti-epidemic regime in hospitals while providing treatment of CHF patients were registered in 2011 (in the Rostov Region) and in 2016 (in the Stavropol Territory). This highlights the need to improve the training of health-care staff for admission of patients with this particularly dangerous infection.